Misleading Tax Figures–A Problem for Accountants. - Weber, Richard P. (The Accounting Review, 1977)
Abstract Some corporate groups that file consolidated returns use different methods to allocate the consolidated tax liability for tax return and financial reporting purposes. Such dual allocations can cause the tax liability reported in an affiliate's financial statements to differ from the liability it reports to the Internal Revenue Service. This is not a "timing" or "permanent" difference as the terms normally are used. Differences arising from dual allocations are the focus of this paper. The paper examines the allocation of consolidated tax liabilities. An illustration is used to demonstrate the allocation methods specified for tax purposes, and the fact that the results of these methods generally do not conform to sound accounting practice is noted. An allocation method consistent with sound accounting practice then is proposed. Finally, the practice of using different allocation methods for tax and financial reporting purposes is examined, and the need for action by the accounting profession in this area is pointed out.